The Gig Economy Across National Borders: Motivations And Economic Impacts (A Study On The Individual Experiences Of Maxim Drivers In Atambua) - Fallo, Adriana R.; Pah, Theny I. B. Kurniati; Rene, Mariayani O.; Long, Belandina L. (JURNAL TRIAS POLITIKA, 2025)
The gig economy trend is increasing and growing in the general public, including in developing countries, especially in a cross-border context. Technological advancements, the growth of the platform-based economy, and changing work patterns and preferences have made gig workers one of the subjects of concern for researchers and governments. Therefore, a comprehensive understanding of gig economy workers is very important, especially in the context of developing countries such as Indonesia, with reference to several important issues such as examining income, job security, and social support. This study examines the income, job security, and social support experienced by gig workers, specifically drivers, in the city of Atambua, a cross-border region in Indonesia. Utilising qualitative methods and purposive sampling, the research involved informants from diverse backgrounds. The findings reveal that supplementary income serves as the primary motivation for individuals engaging in gig work. Additionally, the flexibility in both scheduling and tasks has garnered strong community support for gig workers in Atambua, as their roles contribute significantly to employment absorption. However, job security remains a critical issue, as it is not accounted for within the daily wages earned by these workers. This underscores a notable vulnerability within the gig economy in Atambua.